2016
DOI: 10.1080/23279095.2015.1125904
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Functioning in Huntington’s Disease: A Laboratory-Based Study of Financial Management Capacity

Abstract: One important limitation of prior studies examining functional decline in Huntington's disease (HD) has been the reliance on self-reported measures of ability. Since report-based methods can be biased by lack of insight, depression, and cognitive impairment, contrasting self-reported ability with measures that assess capacity may lead to a more comprehensive estimation of real-world functioning. The present study examined self-reported ability to perform instrumental activities of daily living (iADLs) and perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…We found that cognitive dysfunction was associated with a decrease in financial autonomy at all stages of the disease, which is consistent with the wider literature in other neurodegenerative diseases [ 29 ] including a previous smaller study in HD [ 22 ]. Interestingly, the profile of cognitive deficits was different when looking at financial capacity using the TFC or FA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that cognitive dysfunction was associated with a decrease in financial autonomy at all stages of the disease, which is consistent with the wider literature in other neurodegenerative diseases [ 29 ] including a previous smaller study in HD [ 22 ]. Interestingly, the profile of cognitive deficits was different when looking at financial capacity using the TFC or FA.…”
Section: Discussionsupporting
confidence: 91%
“…Only a small number of studies have looked to describe financial capacity in HD or understand its underlying factors. Sheppard et al [ 22 ] reported a study of 20 HD patients which showed that HD patients were impaired compared to controls on the Advanced Finances Test, which requires participants to pay three bills, deposit a check, and pay off as much of a credit card balance as possible, whilst ensuring that at least $100 is left in their account. Performance was found to correlate with cognition, but not with depression.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms, such as slowed cognitive processing speed, decline in attention, dysexecutive syndrome and irritability/anger outbursts all affect an individual's ability to work, to drive and to manage a household. These symptoms affect the individual with HD even in the pre-manifest stage, with an increasing prevalence of irritability, apathy and executive dysfunction as the disease progresses [10]. The importance of finding effective treatments is clear from both the perspective of the individual with HD and the caregiver, with both groups feeling the impact of these symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have used or developed performance-based tools to assess everyday functioning in HD. Nicoll et al (2014) used the “Memory for Intentions Screening Test” as a standardized performance-based measure of prospective memory in HD and Sheppard et al (2017) used the “Advanced Finances Test” as a performance-based measure of the participants’ ability to manage finances. Both studies were done in semi-naturalistic settings (real materials and props handled in a laboratory) and resorted to observational methods to infer about the mild-moderate HD patients’ performance level.…”
Section: Introductionmentioning
confidence: 99%